Pelatihan Pijat Oketani Ibu Post Partum pada Kader Kesehatan di Wilayah Kerja Puskesmas Tulehu Kabupaten Maluku Tengah - Fasiha, Fasiha; Achmad, Ismiyanti H.; Wabula, Widy Markosia (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Tulehu Community Health Centers is one of the community health centers in these work areas of the Central Maluku Regency Health Services. has 17 Posyandu with 85 active health cadres. There are IYCF Cadres who are representatives of the 17 Posyandu Health cadres. they were formed and trained in 2019. Exclusive breastfeeding coverage in the Tulehu Health Center working area is 32%, which is not yet according to the target of 40%. There were  129 babies, but only 41 people received breast milk. This happens because some mothers say that breast milk production is lacking (insufficient breast milk syndrome), so they give formula milk and additional food before  6 months,  the activity aims is to increase the knowledge and skills of cadres in helping overcome breastfeeding problems in postpartum mothers.  20 cadres were targeted in the activities. The activities carried out consisted of providing oketani massage material demonstrations and re-demonstrations followed by independent practice a home using the learning models/media provided. The post-test results showed that there was an increase in knowledge from 7.1 to 92.26 and the skills assessment results were very good, namely 97.1. This indicates a very good achievement for the participants. It is hoped that regular monitoring and evaluation by midwives of the results of the oketani massage carried out by cadres will result in the problem of breastfeeding being resolved and the coverage of exclusive breastfeeding increasing.